Surface metabolite amino acids and collagen profiling in refrigerated tilapia fish (Oreochromis niloticus): implications for identification and quality assessment - Nuraisah Rabu,; Saiful Irwan Zubairi,; Zainun Nurzahim,; Harisun Yaakob,; Ikhwan Zakaria,; Siti Noor Diana Mohd Kamaruddin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Nile tilapia (Oreochromis niloticus) by-products, including the scales, skin, and mucus, are rich sources of protein with a balanced amino acid profile and high collagen content. Cold storage at 4 ℃ is commonly used to maintain the freshness of tilapia fish in retail settings. This study aims to investigate the changes in surface metabolites and collagen content in tilapia fish during cold storage at 4 ℃. Fresh tilapia fish was stored at 4 ℃ for 7 days to monitor physicochemical and metabolite changes. Fish collagen content was extracted using acetic acid and pepsin, pH values were measured using a calibrated pH meter, protein content was determined via the Bradford method, and creatine and phenylalanine levels were assessed using High-Performance Liquid Chromatography (HPLC). Analysis was conducted on days 0, 3, and 7 of cold storage. Significant reductions (p<0.05) in collagen content from fish scales were observed on the 3rd day of storage, declining from 72.60 ± 12.40% to 30.17 ± 17.62%. pH levels of fish scales and mucus showed a slight alkaline shift, while the skin turned acidic due to bacterial and enzymatic activities. Protein content in the scales, skin, and mucus showed a substantial loss exceeding 50% after 7 days of cold storage. Changes in creatine and phenylalanine concentrations in the mucus further indicated a decline in tilapia fish freshness due to biochemical reactions post-mortem, compromising overall quality. In conclusion, the duration of cold storage significantly affects the composition of tilapia fish scales, skin, and mucus, with a 7-day storage period identified as a suitable freshness indicator in compliance with FDA guidelines permitting fresh fish to be stored at 4 °C for up to two days.